New Target Antigens for Cancer Immunoprevention - Lollini, P.- L.; Nicoletti, G.; Landuzzi, L.; Giovanni, C. D.; Nanni, P. (Current Cancer Drug Targets, 2005)
Prevention of cancer through the activation of the immune system has been explored in recent years in preclinical systems thanks to the availability of several new transgenic mouse models that closely mimic the natural history of human tumors. The most thoroughly investigated model of cancer immunoprevention is the mammary carcinoma of HER-2/neu transgenic mouse. In this system it has clearly been shown that the activation of immune defences in healthy individuals can effectively prevent the subsequent onset of highly aggressive mammary carcinomas. A complete prevention was obtained using a combination of three signals (the so called “triplex” vaccine) that included the specific antigen (p185, the product of HER-2/neu) and nonspecific signals like allogeneic histocompatibility antigens and interleukin 12. The analysis of protective immune responses in models of cancer immunoprevention revealed some unexpected features, in particular the central role of antibodies in immunoprevention, at variance with conventional immunotherapy which is firmly based on cytotoxic T cells. In the HER-2/neu system anti-p185 antibodies, in addition to immunological functions leading to tumor cell lysis, inhibit p185 dimerization and induce its internalization, resulting in the inhibition of mitogenic signaling. Most current tumor antigens appear to be unsuitable targets for cancer immunoprevention. An ideal antigen should have a crucial pathogenetic role in tumor growth to avoid the selection of antigen loss variants. Downregulation of major histocompatibility complex (MHC) expression during tumor progression frequently limits antigen recognition by MHC-restricted T cells. Thus an ideal antigen for cancer immunoprevention should be recognized both by T cells and by antibodies. Antibody binding to cell surface oncogenic determinants, in addition to complement- and cell-mediated tumor cell lysis, can block mitogenic signaling and induce internalization, resulting in tumor growth arrest. A search for new tumor antigens should be conducted among molecules that are directly involved in neoplastic transformation and are recognizable by the immune response also in MHC loss variants. Novel tumor antigens fulfilling both conditions will be crucial for the development of cancer immunoprevention and will provide new targets also for cancer immunotherapy.
Keywords: cancer vaccines